FAMILY WITH A CHRONIC ILLNESS: ADAPTATION AND CHALLENGES - Annisa Wuri Kartika; Wiwin Wiarsih; Henny Permatasari (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2017)
Living with a chronic illness surely can affect clients and their families. Family capacity to adapt successfully can be quite different depend on characteristic of chronic illness and family perception about the illness. Consideration of the family’s view of illness support health care professionals in finding the best resources to assist family with chronic illness. The aim of this study was to describe impact of chronic illness to clients and their family. This research use a qualitative design with descriptive phenomenological approach. Using purposive-sampling, eight families living with chronic illness were participated in this study. Colaizzi’s method which involving participants to validate results was used in the research. The theme of this study are changes in the patient's health status, family system changes and family difficulties in maintenance tasks. Conclusion of this research is that family members are the biggest support to motivate clients and also challenged as they strive to assist member diagnosed with chronic condition to stay healthy. Involving clients and families in the decision making support the efforts of families in their self-management of chronic illness. Thus nurses could provide family counseling to strengthen family coping and capacity by providing family with adequate information about illness.